2012
DOI: 10.4103/0971-9784.91482
|View full text |Cite
|
Sign up to set email alerts
|

Earthing defect: A cause for unstable hemodynamics

Abstract: Interference of monitored electrocardiogram (ECG) is a common event in intensive care units and operation theaters. Artifacts in the ECG tracing can resemble serious arrhythmia, thus leading to unnecessary usage of antiarrhythmics or electrical defibrillation. In addition, ECG artifacts may lead to serious hemodynamic consequences secondary to intra-aortic balloon pump (IABP) trigger failure. We report a rare event of IABP failure due to ECG artifact, which appeared on placement of the transthoracic echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[ 1 ] A related case described ECG artifact on placement of transthoracic echocardiographic probe over the chest due to earthing defect. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] A related case described ECG artifact on placement of transthoracic echocardiographic probe over the chest due to earthing defect. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
“…At times inappropriate earthing or current leakage from the electrical gadgets used during surgery may also interfere with ECG recordings. 8 It is prudent to keep the earthing away from the ECG monitoring sites. Also, the loop of current flow of the electrical gadget probe and its grounded electrode should not cross the heart or the ECG leads.…”
Section: Discussionmentioning
confidence: 99%
“…ECG interference is common throughout hospitals, particularly during cardiac surgery. [7][8][9][10][11][12][13][14][15][16] The authors have observed baseline wander and electrostatic discharge when healthcare providers move hands and torsos in proximity to the patient, tap their feet on the floor, or touch the patient's bed. Such interference can trigger false positive dysrhythmia alarms, signaling ventricular tachycardia and premature ventricular contractions.…”
Section: Introductionmentioning
confidence: 99%